Development of Student Worksheets (LKPD) on Plane Figures Using Indonesian Traditional Houses for Grade IV Elementary/Islamic Elementary School Students - Nurisya Nurisya; Sri Latifah; Anton Tri Hasnanto (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: This study was motivated by the importance of developing valid and practical student worksheets (LKPD) that are student-centered to foster students' interest in learning mathematics. Aim: The study aims to examine the development process of student worksheets (LKPD) on plane figures using Indonesian traditional houses for Grade IV students. In addition, this study also aims to evaluate the feasibility of the LKPD and to assess students' and teachers' responses to the worksheets. Method: This research used a Research and Development (R&D) approach using the ADDIE model. The instrument used for data collection was a questionnaire. Result and discussions: The results show that the average validity scores from the language expert, content expert, and media expert were 95%, 90%, and 96.65%, respectively, all categorized as "highly appropriate." The small-scale trial yielded a total score of 321 out of a maximum of 450, with a feasibility percentage of 71.33%, categorized as "feasible." Meanwhile, the large-scale trial obtained a total score of 883 out of 990, with a feasibility percentage of 89.19%, classified as "highly feasible." Conclusion: Therefore, the LKPD on plane figures using Indonesian traditional houses for Grade IV Elementary/Islamic Elementary School Students meets the criteria for validity and practicality and is suitable for classroom learning.